Transient Hypoparathyroidism in Diabetic Ketoacidosis - Wenhui Zhao; Haiqing Zhu; Zhiqiang Cheng; Bo Zhang; Xiaoyan Xing (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2015)
Introduction: Diabetic ketoacidosispatients frequently develop a constellation of electrolyte disorders. These patientsare markedly potassium-, magnesium- and phosphate-depleted, but hypocalcemia due to transient hypoparathyroidism was seldom reported previously.  Methods: We describe the clinical history, physical examination findings and laboratory values of the patient and briefly review the relevant literature.  Result: A 43-year-old man with a history of diabetes mellitus presented with vomiting, diarrhea and fatigue for 2 days and his laboratory tests showed high serum glucose and diabetic ketoacidosis. CT scan of the abdomen showed no abnormity. Intravenous fluid resuscitation and continuous insulin infusion was initiated. Omeprazole was started for possible upper gastrointestinal hemorrhage. Hypocalcemia, hypophosphatemia, relative hypomagnesemia and transient hypoparathyroidism occurred in the recovering process of diabetic ketoacidosis. There was neither tetany nor spasmin this patient. Two days after the cessation of omeprazole, his serum total calcium, serum phosphateand PTH all returned to normal range.  Conclusion: Physicians should alert transient hypoparathyroidism in diabetic ketoacidosis patients, especially those treated with proton pump inhibitors.